Heterosis and Combining Ability Evaluation in Different Tomato Inbred-lines for Salinity Tolerance During the Seedling Stage - Hamed Kaveh; Safieh vatandoost; Hossein Nemati; Mohammad Farsi (Journal of Epigenetics, 2021)
Vast numbers of studies on tomato breeding have been performed for resistance to environmental stresses and pests. In genetic investigation and breeding of tomato, it is tried to use tomato lines with the most variance on morphological and agronomical traits to obtain better results, like maximum heterosis on F1 hybrids. In this survey combining ability and heterosis of 7 inbred lines (ME, KaLN3, Fla, CT6, LA3770, R2-05, and DB) of tomato and their F1 hybrids were investigated for salinity tolerance during the seedling stage using the diallel-cross. Therefore, seed germination percentage, seedling emergence percent and rate under salt-stress, tested in a complete randomized design with four replications. Results show that the reciprocal effects and SCA  were significant for all traits on the probability of 1 %. Analysis of Wr-Vr regression also shown that seed germination percentage and seedling emergence percentage and rate under salt stress controlled by over-dominance effects. The best line for resistance to salt stress in juvenility was R205, which has the most GCA  for all three traits connected to salt resistance. It may be beneficial to combine this line as a parental line in breeding programs for increasing salinity tolerance of tomato during the seedling stage.